EFFECT OF PERCENTAGE OF RESIN AND CATALYST OF FIBERGLASS FIBER COMPOSITES, WITH FIBER ORIENTATION DIRECTIONS (0°,45°), (45°,90°) AND (0°,90°) ONTENSILE AND IMPACT STRENGTHS - Azis Siregar, Rivaldo; Wulansari, Ajeng; Indrianto Sudjoko, Rifdian (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
In the world of aviation industry the use of composite materials began to be widely developed, one of the most frequentlyused composite materials in the industrial world is composite material with fillers in the form of Fiberglass. Currently,fiber-reinforced composite materials are widely used engineering materials because of their specific strength and stiffness which are far above engineering materials in general, so that their properties can be designed close to the needs. The research conducted used WR 200 Fiberglass with fiber direction orientation treatment (0°, 45°), (45°, 90°), (0°, 90°), with 1%, 1.5%, 2% catalyst. The manufacture of composite workpieces/specimens using the hand lay-up methodwith glass molds measuring 22 cm × 17 cm × 0.4 cm and 10 cm × 5 cm × 1 cm. Based on the tensile and impact tests carried out on the WR 200 fiberglass composite, the tensile test obtained the results with the treatment of fiber direction orientation 45 °, 90 ° with 1% catalyst composition getting the highest tensile strength value of 56.87 N / mm2. The treatment of 0°,90° fiber direction orientation with 2% catalyst composition got the lowest tensile strength value of 38.15 N/mm2. In the impact test, the results obtained with the 45°,90° fiber direction orientation treatment with 1% catalyst composition obtained the highest Fracture Stress value of 9.687 Joules and the highest Tenacity Price value of 0.121 Joules/mm2. The 0°,90 fiber direction orientation treatment with 2% catalyst composition got the lowest fracturestress value of 3,935 Joules and the lowest ductility price value of 0.049 Joules/mm2.